Urbanization: Issues and Impacts on the Village of South 24 Parganas, West Bengal (International Journal of Scientific Research and Management (IJSRM), 2017)
Urban anthropology deals with the social and cultural processes in urban areas as well as cities. Contemporary issues of urban anthropology include rural-urban migration, demography, effects of urbanization among cultural pluralism and practical urban problems. The presents paper depicts the issues and impacts of urbanization on the concentration of rural areas, which has altered human life styles in dramatic and significant ways in a district of West Bengal the preliminary ethnographic account deals with the consequences as well as impact of global urbanization on the rural areas under study in general along with the changing aspects of the socio-cultural milieu. The present study finally depicts the gradual spread of global urbanism in the traditional life in the main stream and surrounding areas of the villages through a micro-ethnographic approach